Influence of fitball aerobics on the development of individual coordinating abilities of girls 14-15 years old - Irina Kyzmenko; Andrzej Ostrowski; Viacheslav Zhuk (Kharkiv State Academy of Physical Culture, 2022)
Purpose: to determine the change in the level of development of the dynamics of the coordination abilities of girls 14-15 years old under the influence of fitball aerobics exercises. Material & Methods: the study was carried out on the basis of general secondary education in Kharkov. It was attended by 46 girls aged 14-15. The following methods were used in the course of the study: theoretical analysis and generalization of scientific and methodological literature, pedagogical testing, pedagogical experiment, methods of mathematical statistics. Results: the level of development of coordination abilities of girls aged 14-15 was assessed by such manifestations of coordination abilities as the ability for spatial orientation, the ability to assess and regulate the spatial and dynamic characteristics of movements, the ability to maintain static balance and the ability to adapt and restructure motor actions. A comparison of the indicators of the development of coordination abilities in the age aspect with the corresponding norms before and after the use of fitball aerobics exercises is presented. The results of the study indicate a trend towards an increase in the level of manifestation of coordination abilities after the experiment. The most significant increase was observed in the indicators of a jump with a turn: from 23,1% to 62,4% and the results of the Bondarevsky test: from 18.6% to 30.6%. Comparison of the indicators of coordination abilities in the age aspect showed that girls of 14 years old in most cases demonstrate higher results than girls of 15 years old. Comparison of the studied indicators with the relevant standards showed that the results correspond to the "average" level. Conclusions: the dynamics of the results indicates the stability of the level of development of coordination abilities and the trend towards their improvement. This confirms the expediency of organizing fitball aerobics classes in the sports section of the school.